Income diversification and working children - Elin Vimefall (Örebro University School of Business, 2015)
During recent years (2004-2008) the proportion of working children in sub-Saharan Africa has increased (Diallo et al. 2010). At the same time, there has been a shift in the patterns of livelihoods, whereby households rely more on sources of income from outside their own farms. When the adult in the household diversifies away from production on their own farm, this is expected to influence the children's time allocation in several ways. In this paper, we investigate how households' income diversification strategy influences children's probabilities of working and going to school among children living in farming households in Kenya, using data from the Kenya Integrated Household Budget Survey 2005/2006. Furthermore, we also analyse child labor at the intensive margin by investigating if the households income diversifications strategy influences the number of hours worked. We find that children living in households that rely solely on the production of their own farms are about 3 percent points more likely to work and about 2 percent points less likely to be in school than children from more diversified households. Furthermore, children living in household who rely only on farming for their income does also work more hours than other children. However, we do not find any differences in the proportions of working children across a number of different income diversification strategies.
Keywords: I25; J13; O12; O15; O55; 330; Income diversification; Child labor; Work; Schooling; Kenya